2014
DOI: 10.1002/smll.201400541
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Nonlinear Optical Properties of Atomically Thin Transition Metal Dichalcogenide Nanosheets

Abstract: Size-dependent nonlinear optical properties of modification-free transition metal dichalcogenide (TMD) nanosheets are reported, including MoS2 , WS2 , and NbSe2 . Firstly, a gradient centrifugation method is demonstrated to separate the TMD nanosheets into different sizes. The successful size separation allows the study of size-dependent nonlinear optical properties of nanoscale TMD materials for the first time. Z-scan measurements indicate that the dispersion of MoS2 and WS2 nanosheets that are 50-60 nm thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 50 publications
12
99
0
Order By: Relevance
“…After initial successes demonstrating the effectiveness of MoS 2 [30] as a saturable absorber in pulsed fibre lasers, recent studies have considered other members of the TMD family of 2D materials, including MoSe 2 , WS 2 and WSe 2 , revealing complementary optical properties and suitability as a high-potential photonic platform. Strong intensity-dependent absorption has been measured, with the magnitude of the nonlinear optical response being found to depend on flake size and thickness, suggesting that few-layer TMD-based devices could be engineered for specific applications [60,62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After initial successes demonstrating the effectiveness of MoS 2 [30] as a saturable absorber in pulsed fibre lasers, recent studies have considered other members of the TMD family of 2D materials, including MoSe 2 , WS 2 and WSe 2 , revealing complementary optical properties and suitability as a high-potential photonic platform. Strong intensity-dependent absorption has been measured, with the magnitude of the nonlinear optical response being found to depend on flake size and thickness, suggesting that few-layer TMD-based devices could be engineered for specific applications [60,62].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that thermal effects under nanosecond or longer optical pulse excitation can lead to effects, including the formation of micro-bubbles, which cause nonlinear scattering. Nonlinear scattering manifests as an optical limiting behaviour similar to RSA [33,60].…”
Section: Other Nonlinear Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…Tailoring the size and dimension of nanomaterials has become one of the most fascinating routes to endow them with novel properties and further broaden their applications . Of significance, transformation from 2D to 0D morphologies occurs when the planar sizes of 2D materials are reduced to below 100 nm for both x‐y dimensions.…”
Section: Introductionmentioning
confidence: 99%